1973
DOI: 10.1161/01.res.32.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Bypass of Xenon in Brain Circulation

Abstract: The diffusion bypass of 188 Xe between arteries and veins was studied in the brains of anesthetized dogs. A mixture of B1 Cr-labeled red cells and 188 Xe was injected as a bolus into the internal carotid artery. Gas-tight venous samples were taken every 0.4-0.8 seconds from the superior sagittal sinus. An excess of 183 Xe in the early venous blood samples over that expected from blood-tissue equilibration considerations was demonstrated in all the experiments. The excess was most marked in the first s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…A possible explanation of the increasing E might be that the test substances bypass the capillaries by diffusion from arteries to veins (shunting), as has been described for 133Xe (14). However, this seems unlikely because the E(t) curves for HOH and propranolol have almost the same slope even though the free diffusion coefficient for HOH is much higher than that for propranolol.…”
Section: Discussionmentioning
confidence: 89%
“…A possible explanation of the increasing E might be that the test substances bypass the capillaries by diffusion from arteries to veins (shunting), as has been described for 133Xe (14). However, this seems unlikely because the E(t) curves for HOH and propranolol have almost the same slope even though the free diffusion coefficient for HOH is much higher than that for propranolol.…”
Section: Discussionmentioning
confidence: 89%
“…If this were the case, some microvessels with higher flow may contribute more oxygen to the venous outflow than microvessels with lower flow. However, there are no favourable conditions for O 2 diffusional shunting in the brain microcirculation [3,7]: cortical arterioles and venules do not form parallel pairs with countercurrent flows as in skeletal muscle. However, only pial arterioles and venules that cross are in immediate contact.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion bypass of 1J3 Xe between arteries and veins has been demonstrated in anesthetized dogs. 18 This could contribute to a small underestimation of cerebral blood flow, particularly in low flow states. Waltz 18 has shown that the washout curves in many experimental animal species can not always be readily resolved into a bimodal pattern, with a fast component representing grey matter flow rates and a slow component representing white matter flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to microsphere use developed in this laboratory has been reported previously. 18 After the completion of each experiment, the animal was sacrificed by the intravenous injection of a saturated solution of KCL. The brain was rapidly removed and wet weight determined.…”
mentioning
confidence: 99%